Perception of Pediatric Outpatient Clinic in Private Hospitals in Semarang City Based on Market Segmentation Characteristics - Dewi Kusuma Wati; Ayun Sriatmi; Septo Pawelas Arso (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Outpatient clinic is a vital hospital service that demands focus on both quality and patient satisfaction. With increasing competition among hospitals in Semarang, understanding consumer behavior is crucial. Market segmentation can assist in identifying patient characteristics and their perceptions of healthcare services, which are shaped by factors such as medical communication, the comfort of facilities, and treatment outcomes. These perceptions significantly influence patients' decisions to seek care again in the future. The pediatric outpatient clinic at XYZ Hospital has experienced inconsistent and relatively low visit rates. Therefore, it is essential to analyze consumer perceptions through segmentation to formulate strategies aimed at increasing patient visits.This research adopts a descriptive qualitative study design, employing a case study approach at XYZ Private Hospital in Semarang. The participants in this study are the parents of pediatric patients. We conducted interviews using questionnaires administered to thirty respondents to gain an overview of their characteristics. We also conducted in-depth interviews with five primary informants to validate the findings. The demographic and geographic data reveal that the average age of parents is 36.03 years (SD 5.25), with 80% of respondents being female and 93.1% residing in Semarang. Additionally, 77.7% hold a bachelor's or master's degree (S1/S2), and 40.74% are employed in the private or entrepreneurial sector. In terms of psychographic and behavioral aspects, 60% of respondents discovered the pediatric clinic through friends or family, while 80% initiated their visits independently. The decision to visit was primarily influenced by the strong reputation of the doctors (60%), and 93.34% utilized personal funds or insurance for payment. Regarding costs, 90% rated outpatient fees as "moderate," with 83.33% agreeing that the costs were commensurate with the quality of service. Furthermore, 53.33% rated all staff services as positive or very positive. Furthermore, 60% found the location to be accessible, 63.33% assessed the facilities as clean, and 80% considered them comfortable.The study indicates that patients hold a positive perception of the pediatric clinic services at XYZ Hospital. They value the reputation of the doctors and the quality of facilities more than cost or location. Positive assessments of service quality, comfort, and cost fairness reflect high levels of satisfaction. Keywords: Segmentation, Patient Perception, Pediatric Outpatient.